Structural modifications in Cs2AgBiBr6 induced by methylammonium substitution: Insights from X-ray diffraction and X-ray absorption fine structure - Han, Sang Wook; Low, Yiin Jian; Talib, Zainal Abidin; Choo, Thye Foo; Sudiro, Toto; Yap, Siew Hong; Liew, Josephine Ying Chyi (Elsevier Ltd, 2025)
Lead-free double perovskites such as Cs₂AgBiBr₆ are promising for sustainable optoelectronics, yet their structural rigidity and limited defect tolerance constrain further optimisation. This study examines the structural evolution of Cs2AgBiBr6 under methylammonium (MA+) substitution to clarify its effects on lattice stability and phase behaviour in Cs2-xMAxAgBiBr6 (x = 0–1.0). X-ray diffraction (XRD)–Williamson–Hall analysis shows that the pristine lattice exhibits high microstrain (1.12 × 10⁻³) and a crystallite size of 38.30 nm. Low substitution (x = 0.2) effectively relieves lattice stress, reducing microstrain to 0.57 × 10⁻³ and decreasing crystallite size to 31.02 nm. Although x = 0.4 yields further microstrain reduction, AgBr impurities emerge, indicating the onset of instability. For x ≥ 0.6, increased microstrain, larger crystallites, and substantial AgBr formation confirm x = 0.2 as the upper limit for stable incorporation. Energy-dispersive X-ray spectroscopy (EDX) results show systematic Ag/Br enrichment and Cs depletion, while X-ray absorption fine structure (XAFS) analysis verifies a stable Bi valence state with higher substitution enhancing local oxidation susceptibility. Overall, moderate MA+ incorporation improves lattice coherence, whereas excessive substitution disrupts structural integrity. These insights address a key structural limitation and support the design of stable, lead-free double perovskites for optoelectronic applications.